The comparison of physical fitness between Thai National badminton players and National youth badminton players - Kerdjuntuk, S.; Kerdjuntuk, N.; Santisewee, S. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Badminton is a highly skill-related sport. Therefore, the players who have good physical fitness will be more likely to get success in the competition. The components of physical fitness for Badminton players are agility, speed, flexibility, strength, power, aerobic and anaerobic capacity combining proportionally for efficient training and competition.